DAMPAK LINGKUNGAN KEGIATAN HUJAN BUATAN DENGAN BAHAN SEMAI Calsium Oxyde (Ca O) STUDI KASUS : KEGIATAN PENELITIAN HUJAN BUATAN DI DAS SAGULING JAWA BARAT PERIODE 10 DESEMBER 1999 S.D. 04 JANUARI 2000 - Widodo, F.Heru (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2000)
Technology of weather modification is one of human interventions to manage atmospheric resources. Other than to increase rainfall, the UPT Hujan Buatan is currently assessing the application of weather modification to lower the intensity of rainfall as inspired by the community. This activity has been applied on two locations: Jratun Seluna Watershed in Central Java and Saguling Watershed in West Java. On assessment of technology for lowering the intensity of rainfall, Calcium Oxide (CaO) was used as a seed material. To analyze whether this material affect negatively to thequality of rain fall and reservoir, a monitoring of the environment was conducted in target areas. This monitoring activity was intended to have an early diagnosis of any changes to qualities of rain fall or the reservoir water that might occur. The method used in this analysis was the comparative method that compares the result analysis of rain fall and reservoir water qualities with a maximum content value according to the PP No. 20 of 1990 for standard water quality type A. The analysis showed that the use of Ca O during modification activity gave no effect on qualities of rain fall and reservoir water because they were still under the maximum limit of standard quality type A, before, during and after the modification activity. In general, rainwater and reservoir water qualities, notably the pH parameter, for areas of Cemara and Banjaran during the activity were still below the maximum limit of standard water quality. This fact may be due to the existence of various industries in the area.